Pembelajaran Bahasa Mandarin Dari Sudut Pandang Sosial Budaya - Aura Fiiha Azhra; Nadiya Sa’adah; Rizqia Azzahra; Yupi Anesti; Siti Hamidah (Universitas Palangka Raya, 2024)
Language cannot be separated from socio-cultural influences because language use is the reality of communication that occurs in social interactions. This article uses the systematic literature review method which in this method uses in-depth review studies and uses references from articles, books and research journals. The purpose of this study is to find out about Chinese language learning from a socio-cultural point of view. Language and culture viewed in balance are significant in foreign language teaching. Successful communication between two communicators from different cultures does not depend on mastery of linguistic aspects, including grammar and sociopragmatic structures, but also on the ability to capture, understand and empathize with the culture of the communication partner. This shows that there is harmony between foreign language and culture and one's own language and culture.